Rumput (Cyperaceae) di Habitat Rawa Bervegetasi Galam di Kecamatan Bati-Bati, Kalimantan Selatan - Siti Sarah; Dharmono Dharmono; Maulana Khalid Riefani (Wahana-Bio: Jurnal Biologi dan Pembelajarannya, 2022)
Cyperaceae has a very large number of members and massive distribution. Species of Cyperaceae live around water and land. The grass (family Cyperaceae) that lives around galam-vegetated swamps in Bati-Batii sub-district has never been studied. Cyperaceae plants can be used as environmental bioindicators. This study to describe the plant species Cyperaceae in the Galam (Melaleuca cajuputi subsp. cumingiana) vegetated swamp. The research method uses a descriptive approach. The research area is a swamp with galam vegetation in Bati-Bati District. There were 5 species of Cyperaceae (Cyperus pilosus, Cyperus pulcherrimus, Eleocharis dulcis, Fimbristylis autumnalis, and Fuirena umbellata). Environmental factors affect the presence of species from Cyperaceae in the Galam vegetated Swamp area.